Validation of the schema coping inventory for dysfunctional coping strategies - Gazzellini, Simone; Pellegrini, Valerio; Napoli, Eleonora; Ventre, Vanessa; Lettori, Donatella; Castelli, Enrico; Basile, Barbara; Giacomantonio, Mauro (Frontiers in Psychology, 2024)
According to the theoretical model of Schema Therapy, each human being has basic needs that require natural satisfaction from childhood. The frustration of such emotional needs leads to the development of early maladaptive schemas (EMS), which in turn are associated with coping styles that represent strategies to deal with the pain caused by activated EMS.The study validates and standardizes the Schema Coping Inventory in the Italian population and evaluates correlations between psychological variables and the SCI.We analysed data from a community sample of 602 Italian adults, aged between 18 and 69 years, who endorsed a structured questionnaire, involving demographic information, the Italian version of the SCI, and an array of theoretically related psychological constructs.Confirmative factor analysis corroborated the tridimensional structure of the SCI (Surrender, Avoidance, Overcompensation), both in terms of the overall goodness-of-fit of the model and the single items' factor loading in the corresponding factors. The internal consistency turned out to be satisfactory.Construct validity has been assessed by convergent and divergent (positive and negative) correlations with the other coping styles' measures and the psychopathological scales administered. Mean values and mean standard deviations are reported for the general population, for psychopathological clinical and non-pathological samples.